Peran Perpustakaan Ngudi Ilmu Ngemplak Dalam Meningkatkan Literasi Informasi Masyarakat Desa - Faaza; Imam Mahmudi (Jurnal Gema Pustakawan, 2025)
This study aims to describe the role of Ngudi Ilmu Ngemplak Library in improving community information literacy and identify factors supporting its implementation. This study employed a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that Ngudi Ilmu Ngemplak Library plays an active role in enhancing community abilities to identify, access, understand, evaluate, and utilize information through social inclusion-based literacy programs, information technology utilization, child-friendly educational services, and community empowerment activities. The success of information literacy development is influenced by librarian competence, village government support, community participation, and technological infrastructure. The study concludes that Ngudi Ilmu Ngemplak Library has become an information literacy center that contributes to improving community knowledge and strengthening lifelong learning opportunities for rural communities.